TEKNOLOGI HIGH PRESSURE PROCESSING (HPP) TERHADAP KEAMANAN MIKROBIOLOGIS DAN KUALITAS PRODUK PANGAN BEKU (FROZEN FOOD): REVIEW JURNAL - Brenario, Stephen Davtaniel; Tahara, Talitha Azmi; Boangmanalu, Tania Roitona; Safitri, Tyara Dewi (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Frozen food is a popular food product due to its long shelf life and ease of preparation. However, conventional freezing processes at high temperatures can reduce nutritional and sensory quality. Non-thermal technologies such as High Pressure Processing (HPP) are innovative solutions to maintain quality without high heating. This article examines the potential application of HPP in frozen food to improve product quality and safety. The method used is a literature review of the latest studies on the working principles, effectiveness, and impacts of HPP on the physical, chemical, and microbiological characteristics of food ingredients. High Pressure Processing (HPP) is able to deactivate pathogenic and spoilage microorganisms at a pressure of 200–600 MPa without damaging sensitive components such as vitamins, proteins, and natural pigments. However, the response of food ingredients to HPP varies depending on their characteristics, such as water content, protein type, and fat content.